2008
DOI: 10.1097/jsa.0b013e318163be50
|View full text |Cite
|
Sign up to set email alerts
|

Spondylolysis and Spondylolisthesis in the Athlete

Abstract: Spondylolysis and spondylolisthesis are common diagnoses made in the athlete suffering from persistent back pain. Although the etiology of this continuum of conditions is uncertain, genetic predisposition and repetitive trauma have been strongly implicated. Sports in which participants are subjected to repetitive hyperextension across the lumbar spine pose a risk for such injuries. Football lineman, oarsmen, dancers, and gymnasts show high rates of these conditions. Treating the athlete with spondylolysis and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 31 publications
0
43
0
1
Order By: Relevance
“…Sports in which participants are subjected to repetitive hyperextension and rotation across the lumbar spine pose a risk for such injury, and football linemen, oarsmen, dancers, gymnasts, and athletes in sports that involve throwing have a high incidence of this condition [1,2] . Two prospective studies have shown that the incidence of low back pain in athletes with spondylolysis was 72.5% in high school rugby players, 79.8% in high school football players, and 80.5% in college football players [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…Sports in which participants are subjected to repetitive hyperextension and rotation across the lumbar spine pose a risk for such injury, and football linemen, oarsmen, dancers, gymnasts, and athletes in sports that involve throwing have a high incidence of this condition [1,2] . Two prospective studies have shown that the incidence of low back pain in athletes with spondylolysis was 72.5% in high school rugby players, 79.8% in high school football players, and 80.5% in college football players [3,4] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been observed that physically active adolescents with a history of participation in competitive sports may develop nonunion. 58 This was the case for 6 (75%) of the 8 patients in our series who could recall the onset of their symptoms in correlation with competitive sporting activity ( Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…[24][25][26]47,48,65 Pain typically manifests as axial low-back pain but often is noted to have radiculopathic features exacerbated by hyperextension. 58 Diagnosis is most commonly performed by oblique radiographs of the lumbar spine. However, many nondisplaced pars fractures may not be evident on plain radiographs, and CT has been the mainstay of fracture identification and preoperative planning (Fig.…”
mentioning
confidence: 99%
“…Human anatomy, body morphotype [6,7] and professional strengths [8,9] may induce several biomechanical changes in spinal column [5,[10][11][12]. Thus, abnormalities of PI (pelvic incidence) may compromise spinal sagittal balance [13] and seem to be a major parameter in degenerative spinal disease when analyzing the pathogenesis of lumbar spondylolisthesis.…”
Section: Introductionmentioning
confidence: 99%